TadA-mediated A-to-I mRNA editing rewires redox metabolism to promote dominance of epidemic Klebsiella pneumoniae clones - Xingyu Wu; Longyang Jin; Qi Wang; Ruobing Wang; Bowen Li; Chongyang Jiang; Kaiwen Song; Long Chen; Guankun Yin; Fengning Chen; Xiaoyun Liu; Hui Wang (Proceedings of the National Academy of Sciences, 2026)
Dominant carbapenem-resistant Klebsiella pneumoniae (CRKP) clones have markedly intensified the burden of invasive infections while severely restricting treatment options. Although genomic determinants of these high-risk lineages are well characterized, adaptive regulatory mechanisms beyond fixed DNA variation remain poorly understood. Here we systematically map the adenosine-to-inosine (A-to-I) mRNA editing landscape in CRKP and reveal that clinically dominant lineages possess a constrained and clone-specific landscape of RNA editing. We identify PncR (a previously uncharacterized AraC/XylS family transcription factor) and the response regulator DcuR as prominent A-to-I editing targets enriched in high-risk clones. Editing of these regulators reshapes redox and metabolic programs, thereby increasing tolerance to oxidative stress associated with innate immune attack. These results support a model in which stress-responsive RNA editing promotes stress adaptation specifically in high-risk CRKP clones. Furthermore, we demonstrate that the tRNA deaminase TadA is the sole A-to-I editing enzyme in K. pneumoniae , and that its abundance determines both the extent and diversity of mRNA editing. These findings establish TadA-driven A-to-I editing as a selectable, posttranscriptional regulatory layer that reshapes bacterial metabolism and promotes the success of high-risk CRKP lineages, highlighting this axis as a potential target for therapeutic intervention.